COMBUSTION ANALYSIS OF MULTI-CIRCULAR JET PLATE IN INTERNAL MIXING AIR-ASSISTED ATOMIZER OF BURNER SYSTEM - Amirnordin, S.H.; Khalid, A.; Sulaiman, S.; Jacob, D.W.; Fawzi, M.; Seri, S.M. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
Multi-Circular Jet (MCJ) plates have been identified as a turbulence generation system that can improve the performance of combustion. Most of the previous studies focused on the passive control method involve the changes in initial conditions of the systems including the geometry. However, the effects of primary air entrance of MCJ plates need to be investigated further. This paper aims to determine the effects of MCJ plates geometry on the burner combustion using the flame visualization technique. The plates are represented by P1, P2, and P3 characterized by the difference in the open area ratio at 17.8, 18.4 and 18.9 respectively. In the experiments, the flame images of all plates are captured at equivalence ratios of 0.8 to 1.2 using a Digital Single Lens Reflect camera. The flame temperatures are measured using the infra-red imaging technique while the emissions, burning chamber and stack temperature are also recorded using an emission gas analyzer and K-type thermocouples respectively. Image processing technique was used to analyze the data. Results show that an increase in open area ratio increases the flame temperature up to 11.4%. The result indicates that the open area ratio of the MCJ plates is significant to the flame characteristics of the burner combustion.